2015
DOI: 10.1021/jacs.5b02576
|View full text |Cite
|
Sign up to set email alerts
|

Rate Law Analysis of Water Oxidation on a Hematite Surface

Abstract: Water oxidation is a key chemical reaction, central to both biological photosynthesis and artificial solar fuel synthesis strategies. Despite recent progress on the structure of the natural catalytic site, and on inorganic catalyst function, determining the mechanistic details of this multiredox reaction remains a significant challenge. We report herein a rate law analysis of the order of water oxidation as a function of surface hole density on a hematite photoanode employing photoinduced absorption spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
405
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 304 publications
(446 citation statements)
references
References 47 publications
38
405
3
Order By: Relevance
“…36 Similar to this study, a third order reaction was also observed (above a surface hole density threshold). Ma et.…”
Section: Possible Water Oxidation Mechanisms On Titaniasupporting
confidence: 86%
See 2 more Smart Citations
“…36 Similar to this study, a third order reaction was also observed (above a surface hole density threshold). Ma et.…”
Section: Possible Water Oxidation Mechanisms On Titaniasupporting
confidence: 86%
“…This novel approach was recently used to examine the reaction kinetics, and thus deduce the rate law with respect to holes, for the photocatalytic oxidation of water on α-Fe2O3 in alkali 36 and on BiVO4 in neutral pH. 37 Using PIAS, we investigate the water oxidation reaction on anatase TiO2 in acid, neutral and alkali pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial photocurrent decay most probably derives from a decrease in band bending due to hole accumulation, reducing the photoanode charge separation efficiency, as discussed previously. 11 When the excitation light is switched off, the OD signal decays to zero on the seconds timescale, with the slow timescale of this decay being assigned primarily to slow water oxidation by these surface holes, as discussed further below. In contrast, the current decreases to zero rapidly with no negative current transients, indicative of negligible losses from surface back electron/hole recombination under the strongly anodic bias conditions employed.…”
Section: -28mentioning
confidence: 97%
“…The reaction kinetics were obtained using the rate law analysis employed previously for hematite photoanodes. 11 These data are compared against those obtained using potassium ferrocyanide (K4[Fe(CN)6]) as a facile hole scavenger.…”
Section: Toc Graphicsmentioning
confidence: 99%